1988
DOI: 10.1002/sia.740130210
|View full text |Cite
|
Sign up to set email alerts
|

An x‐ray photoelectron spectroscopic study of some chromium–oxygen systems

Abstract: A series of pure and mixed chromium standards has been analysed by x-ray photoelectron spectroscopy in order to obtain a sdiciently homogeneous and self-consistent set of spectral parameters to be used in the resolution of complex spectra. Additional information was obtained about the stability of the various species under Ar ion bombardment. The results relevant to potassium chromate and dichromate, chromous acid, chromium (111) oxide, hydroxide a d nitrate are described and compared critically with those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(70 citation statements)
references
References 18 publications
9
60
0
Order By: Relevance
“…High intensity peak at 576.9 eV corresponds to Cr 2p 3/2 and other peak at 586.6 eV to Cr 2p 1/2 . [10][11][12] The difference in BE between these two peak is 9.7 eV which is close to the reported value. 10) With increase of sputtering time, intensity of the Cr peak increases and the peak position remains unchanged.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…High intensity peak at 576.9 eV corresponds to Cr 2p 3/2 and other peak at 586.6 eV to Cr 2p 1/2 . [10][11][12] The difference in BE between these two peak is 9.7 eV which is close to the reported value. 10) With increase of sputtering time, intensity of the Cr peak increases and the peak position remains unchanged.…”
Section: Resultssupporting
confidence: 85%
“…The peaks at BE 576.6 eV and 577.5 eV were assigned to chromium oxide (Cr 2 O 3 ). 12,13) and chromium hydroxide (Cr(OH) 3 ), 14) respectively. While the peak at BE of 575.6 eV corresponding to Cr-N bonding.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS investigation made in the present work (Fig. S3) has revealed that the surfaces correspond to The complexity of the C1s reference peaks, however, hinders a precise peak positioning and a distinction between Cr(OH) 3 and Cr 2 O 3 was not possible due to the proximity of the corresponding binding energies [41,42]. Thus, we assume that the temperature increase induced by light absorption, in this case, promotes amorphous-Cr 2 O 3 (or a mixture of oxides) to transform into the more thermodynamically stable crystallineCr 2 O 3 .…”
Section: Surface Characterizationmentioning
confidence: 64%
“…Doublet 1 + 2: Cr metal; doublet 3 + 4: Cr(III) oxide; doublet 5 + 6: Cr(III) hydroxide; doublet 7 + 8: potassium dichromate [27].…”
Section: Figurementioning
confidence: 99%